A Lithiated Perfluorinated Sulfonic Acid Polymer Electrolyte for Lithium-Oxygen Batteries. Issue 9 (14th July 2017) - Shi, Yanqiong; Wu, Chaolumen; Li, Lei; Yang, Jun
Abstract : A novel polymer electrolyte based on lithiated perfluorinated sulfonic acid ionomer (PFSA-Li) and poly(tetrafluoroethylene) (PTFE) was prepared, and its performance in the Li-O2 batteries was evaluated. In this polymer electrolyte, porous PTFE membrane was used as supporting substrate to provide mechanical strength and dimensional stability, and PFSA-Li ionomer was employed as polymer electrolyte to fill into the pores of the PTFE substrate. After swollen with anhydrous dimethyl sulfoxide solvent, the PFSA-Li/PTFE polymer electrolyte showed a high room temperature ionic conductivity of 1.5 × 10 −4 S cm −1 and a high lithium transference number of 0.84. Its use in a lithium-oxygen battery demonstrated excellent compatibility to lithium anode with stable interface property and dendrite-free Li deposition. A good cycling stability over 90 cycles at 1000 mAh g −1 and rate capability up to 2 A g −1 were obtained suggesting a feasible strategy for developing large-scale Li-O2 battery systems toward high energy and high power application with polymer electrolytes.